Analysis of Educational Facilities and Infrastructure Management in Improving Learning Effectiveness: A Literature Review - Elya Siska Anggraini; Dwie Nola Wardani; Khoirun Nisa; Mia Julafni; Nayla Amanda Nasution (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to examine the concept of educational facilities and infrastructure management and its role in improving the effectiveness of learning. The research employed a library research method by reviewing various literature sources such as books, scientific journals, and academic articles relevant to the research topic. Data collection was conducted through literature review and analysis of sources related to educational facilities and infrastructure management. The collected data were analyzed using a qualitative descriptive approach to obtain a comprehensive understanding of the concepts, roles, and management principles of educational facilities and infrastructure. The results of the study indicate that educational facilities and infrastructure play an important role in supporting effective learning. Proper, efficient, and sustainable management of facilities and infrastructure can create a conducive learning environment, increase students’ learning motivation, and assist teachers in delivering learning materials more effectively. Therefore, effective management of educational facilities and infrastructure becomes an important factor in improving the quality of the learning process in educational institutions.